Evolution and mechanistic insights of platelet-derived products in temporomandibular joint regeneration - Lin, Cong; Jin, Yutong; Li, Dan; Yang, Quanquan; Chen, Tingyao; Chen, Quan; Zhang, Mubin; Long, Zhangbiao; Fang, Dongdong (Frontiers in Cell and Developmental Biology, 2026)
Temporomandibular disorders (TMDs) and end-stage osteoarthritis are among the most common disabling diseases of the oral and maxillofacial region. Due to its unique fibrocartilaginous structure and limited vascularization, the temporomandibular joint (TMJ) possesses an extremely limited intrinsic regenerative capacity. Unlike conventional treatments that predominantly address symptoms, autologous platelet-derived products (APDs), such as platelet-rich plasma, platelet-rich fibrin, and concentrated growth factors, have been increasingly investigated for their biological roles in TMJ repair by mimicking natural healing mechanisms. This review summarizes the technical evolution of APDs and elucidates the molecular mechanisms promoting TMJ regeneration. Specifically, it discusses how APDs modulate the TMJ microenvironment by driving mesenchymal stem cell proliferation, directing chondrogenic differentiation, and resolving inflammation through immunomodulatory cascades. In addition, this review discusses the relevance of rheological properties for stage-specific clinical application and outlines translational considerations for the use of APDs in the management of TMDs.